Diversity of Babesia and Theileria species in symptomatic and asymptomatic dogs in Croatia - Beck, Relja; Vojta, Lea; Mrljak, Vladimir; Marinculić, Albert; Beck, Ana; Živičnjak, Tatjana; Cacciò, Simone M. (International journal for parasitology, 2009)
Babesiosis, the disease caused by tick-borne hematozoan parasites of the genus Babesia, is particularly common in dogs, and is caused by several “large” species of Babesia, as well as by an increasing number of “small” species of Babesia, some of which appear to be more closely related to members of the genus Theileria. In this work, blood samples were collected from 848 randomly selected, asymptomatic dogs and from 81 symptomatic dogs, microscopically positive for Babesia, and characterised by PCR and sequence analysis of a fragment of the ssrRNA gene. A prevalence of 3.42% (29 of 848) was found in asymptomatic dogs and sequence analysis revealed the presence of Babesia canis canis in 20 dogs (69%), Babesia gibsoni in six dogs (21%), Babesia canis vogeli in two dogs (7%) and Theileria annae in one dog (3%). In the group of symptomatic dogs, which were all positive by PCR, B. canis canis was the predominant species (78 dogs, or 96%), followed by single infections with B. canis vogeli, Babesia caballi and Theileria equi. Our study has confirmed that dogs are infected with a wide range of both large and small piroplasm species and subspecies, including B. caballi and T. equi, two parasites usually found in horses. The detection of the pathogenic species B. canis canis and B. gibsoni in asymptomatic dogs indicates that the relationship between parasite species/subspecies and clinical signs of infection in dogs deserves further investigation. Finally, the identities of the tick vectors transmitting T. annae and B. caballi remain to be elucidated.